2019
DOI: 10.3892/or.2019.6974
|View full text |Cite
|
Sign up to set email alerts
|

Wnt7a predicts poor prognosis, and contributes to growth and metastasis in tongue squamous cell carcinoma

Abstract: Regional and distant metastases are the principal reasons underlying the high mortality rate associated with tongue squamous cell carcinoma (TSCC); however, the precise molecular mechanisms involved in tongue tumorigenesis remain unknown. The present study aimed to determine the expression and mechanism of regulation of Wnt7a in the growth and metastasis of TSCC. Wnt7a mRNA and protein expression levels were examined in TSCC tissues using reverse transcription-quantitative polymerase chain reaction and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As stated above, we annotated the type 2 immunity GEP based on its association with IL-4 and IL-13, as well as ADIPOQ, in both compressed screens. Reassuringly, we found that IFN-γ was associated with the IFN-γ response GEP, IFN-α2 was associated with the type I IFN signaling GEP, TGF-β and INHBB (a member of the TGF-β superfamily) with the TGF-β response GEP, IL-1A, IL-1B, and TNF-α (known activators of NF-κβ 26 ) with the NF-κβ activation GEP, and the mitogens WNT7A and RSPO3 were associated with the ribosomal GEP 27,28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated above, we annotated the type 2 immunity GEP based on its association with IL-4 and IL-13, as well as ADIPOQ, in both compressed screens. Reassuringly, we found that IFN-γ was associated with the IFN-γ response GEP, IFN-α2 was associated with the type I IFN signaling GEP, TGF-β and INHBB (a member of the TGF-β superfamily) with the TGF-β response GEP, IL-1A, IL-1B, and TNF-α (known activators of NF-κβ 26 ) with the NF-κβ activation GEP, and the mitogens WNT7A and RSPO3 were associated with the ribosomal GEP 27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…As stated above, we annotated the type 2 immunity GEP based on its association with IL-4 and IL-13, as well as ADIPOQ, in both compressed screens. Reassuringly, we found that IFN-γ was associated with the IFN-γ response GEP, IFN-ɑ2 was associated with the type I IFN signaling GEP, TGF-β and INHBB (a member of the TGF-β superfamily) with the TGF-β response GEP, IL-1A, IL-1B, and TNF-α (known activators of NF-κβ 26 ) with the NF-κβ activation GEP, and the mitogens WNT7A and RSPO3 were associated with the ribosomal GEP 27,28 . Interestingly, we would not have been able to infer which ligands were most active in the organoids by examining cognate receptor expression, given our active ligands spanned the range of cognate receptor expression in negative control organoid cells (Extended Data Fig.…”
Section: Compressed Tumor Microenvironment Ligand Screening With Pdac...mentioning
confidence: 99%
“…The 5-years survival rate of advanced TSCC is approximately 50% (Fan et al, 2018). In addition, there are currently no effective drugs available to treat TSCC in situ and inhibit the distant metastases in the early stage (Jia B. et al, 2019). Therefore, it is urgent to experimentally screen out drugs that effectively inhibit the invasion and metastasis of TSCC, which could be applied clinically to prevent tumors to spread and improve the survival rate of patients eventually (Fan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tongue squamous cell carcinoma (TSCC) represents the most frequent type of oral squamous cell carcinoma (OSCC) and is famous for its high potential of metastasis and proliferation 1‐5 . TSCC usually leads to speech, deglutition and mastication malfunction 6‐8 . Despite the advancement in radiotherapy, chemotherapy and surgery, the 5‐year survival rate of this disease is still not satisfactory 9‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advancement in radiotherapy, chemotherapy and surgery, the 5‐year survival rate of this disease is still not satisfactory 9‐12 . Survival rate improvement requires more understanding of initiation and progression of TSCC 6,13,14 . Therefore, more works should be performed to explain the molecular mechanisms and process, which may identify new effective targets for TSCC treatment.…”
Section: Introductionmentioning
confidence: 99%